2007
DOI: 10.1093/dnares/dsm025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Soybean Genome Using EST-derived Microsatellite Markers

Abstract: We generated a high-density genetic linkage map of soybean using expressed sequence tag (EST)-derived microsatellite markers. A total of 6920 primer pairs (10.9%) were designed to amplify simple sequence repeats (SSRs) from 63 676 publicly available non-redundant soybean ESTs. The polymorphism of two parent plants, the Japanese cultivar ‘Misuzudaizu’ and the Chinese line ‘Moshidou Gong 503’, were examined using 10% polyacrylamide gel electrophoresis. Primer pairs showing polymorphism were then used for genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
105
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 30 publications
15
105
5
Order By: Relevance
“…The homeologous duplicated regions were investigated by gel-blot analysis with RFLP markers (Shoemaker et al 1996;Tsubokura et al 2008) and EST-derived SSR markers (Hisano et al 2007). GmPhyA1 and -2 were located on LG I and O, and these linkage groups shared the homeologous duplicated region (Shoemaker et al 1996;Hisano et al 2007;Liu et al 2008;Tsubokura et al 2008). Information obtained from the database LIS, together with previous studies, has shown that a part of LG L and N might be homeologous.…”
Section: Discussionmentioning
confidence: 99%
“…The homeologous duplicated regions were investigated by gel-blot analysis with RFLP markers (Shoemaker et al 1996;Tsubokura et al 2008) and EST-derived SSR markers (Hisano et al 2007). GmPhyA1 and -2 were located on LG I and O, and these linkage groups shared the homeologous duplicated region (Shoemaker et al 1996;Hisano et al 2007;Liu et al 2008;Tsubokura et al 2008). Information obtained from the database LIS, together with previous studies, has shown that a part of LG L and N might be homeologous.…”
Section: Discussionmentioning
confidence: 99%
“…A total 23 SSR primers derived from soybean sequences. Hisano et al [12] were used in this study. PCR analysis was performed in a total volume of 15 μl that contained 20 ng/µl of genomic DNA, 0.25 μM of each primer (forward and reverse), 0.125 mM of each dNTPs, 0.15 units of TaqDNA polymerase, and 1 × reaction buffer.…”
Section: Dna Extraction and Ssr Analysismentioning
confidence: 99%
“…Recently, the usage of soybean for biodiesel has made this crop more economically important, and the whole-genome sequencing of Williams 82 (G. max) and IT182932 (G. soja) have been completed accordingly (Hisano et al, 2007;Kim et al, 2010;Schmutz et al, 2010). Yu & Kiang (1993) reported that Korea might be one of the major center of soybean origins based on electrophoretic assays of wild soybean (G. soja) and cultivated soybeans (G. max).…”
mentioning
confidence: 99%